A randomized phase II trial evaluating the addition of low dose, short course sunitinib to docetaxel in advanced solid tumours - Ang, Yvonne L. E.; Ho, Gwo Fuang; Soo, Ross A.; Sundar, Raghav; Tan, Sing Huang; Yong, Wei Peng; Ow, Samuel G. W.; Lim, Joline S. J.; Chong, Wan Qin; Soe, Phyu Pyar; Tai, Bee Choo; Wang, Lingzhi; et al. (BMC cancer, 2020)
Background We previously reported that low-dose, short-course sunitinib prior to neoadjuvant doxorubicin-cyclophosphamide (AC) normalised tumour vasculature and improved perfusion, but resulted in neutropenia and delayed subsequent cycles in breast cancer patients. This study combined sunitinib with docetaxel, which has an earlier neutrophil nadir than AC. Methods Patients with advanced solid cancers were randomized 1:1 to 3-weekly docetaxel 75 mg/m 2 , with or without sunitinib 12.5 mg daily for 7 days prior to docetaxel, stratified by primary tumour site. Primary endpoints were objective-response (ORR:CR + PR) and clinical-benefit rate (CBR:CR + PR + SD); secondary endpoints were toxicity and progression-free-survival (PFS). Results We enrolled 68 patients from 2 study sites; 33 received docetaxel-sunitinib and 35 docetaxel alone, with 33 breast, 25 lung and 10 patients with other cancers. There was no difference in ORR (30.3% vs 28.6%, p = 0.432, odds-ratio [OR] 1.10, 95% CI 0.38–3.18); CBR was lower in the docetaxel-sunitinib arm (48.5% vs 71.4%, p = 0.027 OR 0.37, 95% CI 0.14–1.01). Median PFS was shorter in the docetaxel-sunitinib arm (2.9 vs 4.9 months, hazard-ratio [HR] 2.00, 95% CI 1.15–3.48, p = 0.014) overall, as well as in breast (4.2 vs 5.6 months, p = 0.048) and other cancers (2.0 vs 5.3 months, p = 0.009), but not in lung cancers (2.9 vs 4.1 months, p = 0.597). Median OS was similar in both arms overall (9.9 vs 10.5 months, HR 0.92, 95% CI 0.51–1.67, p = 0.789), and in the breast (18.9 vs 25.8 months, p = 0.354), lung (7.0 vs 6.7 months, p = 0.970) and other cancers (4.5 vs 8.8 months, p = 0.449) subgroups. Grade 3/4 haematological toxicities were lower with docetaxel-sunitinib (18.2% vs 34.3%, p = 0.132), attributed to greater discretionary use of prophylactic G-CSF (90.9% vs 63.0%, p = 0.024). Grade 3/4 non-haematological toxicities were similar (12.1% vs 14.3%, p = 0.792). Conclusions The addition of sunitinib to docetaxel was well-tolerated but did not improve outcomes. The possible negative impact in metastatic breast cancer patients is contrary to results of adding sunitinib to neoadjuvant AC. These negative results suggest that the intermittent administration of sunitinib in the current dose and schedule with docetaxel in advanced solid tumours, particularly breast cancers, is not beneficial. Trial registration The study was registered ( NCT01803503 ) prospectively on clinicaltrials.gov on 4th March 2013.